Consensus on the utility of bone markers in the malignant bone disease setting - Coleman, R.; Costa, L.; Saad, F.; Cook, R.; Hadji, P.; Terpos, E.; Garnero, P.; Brown, J.; Body, J.-J.; Smith, M.; Lee, K.-A.; Major, P.; et al. (Critical Reviews in Oncology/Hematology, 2011)
Biochemical markers of bone turnover provide insight into ongoing rates of skeletal metabolism and tumor-bone interactions in patients with malignant bone disease. This article reviews the available recent evidence assessing the potential of bone markers for detecting and monitoring malignant bone lesions in patients with advanced cancers, and for assessing overall skeletal health and response to antiresorptive therapies in patients at all stages of cancer progression. Most data thus far are for urinary N-terminal cross-linked telopeptide of type I collagen (NTX) in predicting risks of skeletal morbidity and death and monitoring response to zoledronic acid in patients with bone metastases. Ongoing studies are evaluating such correlations for other markers and therapies. Emerging evidence suggests that bone markers may help identify patients at high risk for bone metastasis or bone lesion progression, thereby allowing improved follow-up. Results from ongoing clinical trials evaluating such potential applications of bone markers are awaited. © 2011 Elsevier Ireland Ltd.
Keywords: Antiresorptive; Bisphosphonate; Bone marker; Bone metastasis; Bone turnover; Cancer; Osteolysis